44. In-host Infection Dynamics Of Pseudomonas Aeruginosa Pneumonia. (31st December 2020) - Bachta, Kelly E R; Allen, Jonathan P; Hauser, Alan R
Abstract: Background: Pseudomonas aeruginosa (PA) is an important cause of healthcare-associated infections including pneumonia and bloodstream infections (bacteremia). PA pneumonia is a significant cause of morbidity and mortality, especially in immunocompromised patients and those on prolonged mechanical ventilation; However, little is known about the in-host infection dynamics of PA pneumonia and its relationship to transmission. Methods: We utilized a mouse model in conjunction with sequencing technology to dissect the infection dynamics of PA pneumonia. BALB/c mice were challenged intranasally with a clinical isolate, PABL012. At various time points post infection, organs were harvested and the surviving PA enumerated. STAMP (sequence tag-based analysis of microbial populations) analysis was applied to define the in-host infection dynamics. Results: Bacterial enumeration revealed that PA disseminates early and widely in intranasally infected animals. Infected mice shed significant amounts of PA in their gastrointestinal tract (GI). Finally, STAMP analysis revealed that compared to bloodstream infections where PA experiences a severe in vivo bottleneck when trafficking to GI tract, PA disseminates freely from the lungs to the GI tract with little bottleneck effect. Conclusion: Our research, using murine models, sheds light on the infection dynamics of PA pneumonia. Our results suggest that the lungs are a unique environment in which PA replicates unchecked and experiences little bottleneck effect. This unchecked replication likely seeds the gastrointestinal tract and promotes significant fecal excretion. Fecal excretion of PA from hospitalized patients is observed, but the direct link between pneumonia, GI shedding, and transmission remains unclear. Our observations have significant implications for infection control and shed light on how PA might exit the human host into the healthcare environment setting the stage for a transmission event. Disclosures: All Authors : No reported disclosures